DEVELOPMENT METHODS FOR CALCULATING POWER LOSSES AND THE VOLTAGE LEVELS IN COMPLEX DISTRIBUTION NETWORKS - I. M. Valeev (Известия высших учебных заведений: Проблемы энергетики, 2017)
The paper presents an analysis and evaluation of the effectiveness different methods for reduction the power loss and voltage in the distribution networks by changing and building a new network topology using the software PSS/ADEAPT. We developed and applied the new algorithm for calculating distribution circuit. The calculation results by the software show that a change network topology is highly effective in practice and applicable to any mode of network operation.